2017
DOI: 10.1002/jemt.22848
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale electrical properties of ZnO nanorods grown by chemical bath deposition

Abstract: Well-aligned zinc oxide nanorod arrays (ZNAs) synthesized using chemical bath deposition were fabricated on a gallium-doped zinc oxide substrate, and the effects of varying the precursor concentrations on the growth and nanoscale electrical properties of the ZNAs were investigated. The as-synthesized ZNAs were characterized using field-emission scanning electron microscopy (FESEM), atomic force microscopy (AFM), conducting atomic force microscopy (CAFM), and scanning surface potential microscopy (SSPM). The FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The unexpected alternate in the aspect ratio may additionally be due to a clear distinction in average diameter and the average length of the ZnO NRs in each method of synthesis. The behavior aspect ratio variation in the absence of air bubbles is in good agreement with the previous studies [31,34,41]. From Figure 3c, we noticed that the higher aspect ratio is corresponding to the precursor concentration of 0.05 M. The ZnO NRs grown with higher aspect ratio created well-aligned ZnO NRs [37,38,54].…”
Section: Morphology Characteristicssupporting
confidence: 91%
See 2 more Smart Citations
“…The unexpected alternate in the aspect ratio may additionally be due to a clear distinction in average diameter and the average length of the ZnO NRs in each method of synthesis. The behavior aspect ratio variation in the absence of air bubbles is in good agreement with the previous studies [31,34,41]. From Figure 3c, we noticed that the higher aspect ratio is corresponding to the precursor concentration of 0.05 M. The ZnO NRs grown with higher aspect ratio created well-aligned ZnO NRs [37,38,54].…”
Section: Morphology Characteristicssupporting
confidence: 91%
“…In addition, the obtained ZnO NRs had wurtzite hexagonal crystal structure and grown with c-axis [40]. The influence of different precursor concentrations (0.01-0.07 M) on the morphology, structure and nanoscale electrical properties of well-aligned ZnO NRs grown on gallium-doped ZnO substrate by CBD process was observed by Chen et al [41]. It was found that intensity; average length, and average diameter increased as the precursor concentrations are increased.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation